Effect Of Easy In The Use, Trust And Benefits Of The Use Of Mobile Banking Services - Putu Gede Wibi PREDANA; A.A. Ketut JAYAWARSA; A.A. Sri PURNAMI; Gde Deny LARASDIPUTRA; Komang Adi Kurniawan SAPUTRA (Indonesia Strategic Sustainability, 2020)
Mobile Banking, also known as M-Banking and SMS banking is a terminal used for checking balances, financial transactions, payments using mobile devices such as cell phones. Mobile Banking is currently mostly demonstrated via SMS or Mobile Internet but can also use mobile device download programs. This study aims to determine the effect of Ease of Use, Trust, and Benefits of Using Mobile Banking Services on Students of the Faculty of Economics and Business, Warmadewa University. The research method uses a questionnaire while data analysis uses multiple linear regression. The research sample was 50 mobile banking users. The results of this study indicate that ease of use has a positive and significant effect on the use of mobile banking services, trust has a positive and significant effect on the use of mobile banking services, and benefits have a positive and significant effect on usage. mobile banking services.